Gastroesophageal reflux disease in voice disorders: screening and correlating symptoms and signs in 100 Egyptian voice patients - Mohammed Aly Saad Baraka; Hend Mohamed Alhanafy; Rasha Mohamed Shoeib; Mona Sameeh Khodeir (The Egyptian Journal of Otolaryngology)
Abstract Objectives The prevalence of GERD in patients with voice disorders varies significantly across studies. Additionally, no clear link exists between laryngoscopic findings and symptoms of GERD and LPR in adults. Thus, this study aimed to screen the prevalence and correlation of GERD symptoms and signs in Egyptian patients with voice disorders. Methods This study screened 100 patients with voice disorders for symptoms and signs of GERD using the Arabic Reflux Symptom Index (A-RSI) and the Reflux Finding Score (RFS). Results Results showed that 18% of patients had suggestive symptoms and signs of GERD. The most frequently reported GERD symptoms were hoarseness, throat clearing, and globus sensation. The observed signs were erythema, edema, and mucus. No significant correlation was found between A-RSI and RFS scores, suggesting that these symptoms and signs may not be specifically related to GERD. The study found higher GERD prevalence among males, older individuals, those who experienced longer durations of voice complaints, and patients with minimal associated pathological lesions (MAPLs). Conclusion This study concluded that phonasthenia (voice fatigue) and the presence of voice lesions, rather than GERD, were strongly associated with the observed symptoms and signs among the participating patients with voice disorders.